2020
DOI: 10.1399/eps.2020.318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal manipulation during incubation and heat challenge during the early juvenile stage on production parameters of broilers reared under a tropical climate

Abstract: Heat stress induces economics losses in poultry production. Several studies have shown that this negative effect can be reduced by heat treatments like thermal manipulation during incubation (TMI) and early age thermal conditioning (ETC). The aim of this study was to investigate the effects of TMI on embryo development and the effects of TMI and ETC on productive performances of broilers under a tropical climate. The study involved 1000 Ross 308 broiler hatching eggs incubated at standard incubation conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 19 publications
4
14
0
Order By: Relevance
“…Also, other studies (Meteyake et al, 2020;Oke et al, 2020) indicated that and early age thermal manipulation improved the performance and thermotolerance of broiler under thermal stress.…”
Section: Management Strategiesmentioning
confidence: 90%
See 1 more Smart Citation
“…Also, other studies (Meteyake et al, 2020;Oke et al, 2020) indicated that and early age thermal manipulation improved the performance and thermotolerance of broiler under thermal stress.…”
Section: Management Strategiesmentioning
confidence: 90%
“…Embryonic thermal manipulation may use to prevent broilers from thermally induced oxidative stress (Saleh et al., 2020). Also, other studies (Meteyake et al., 2020; Oke et al., 2020) indicated that and early age thermal manipulation improved the performance and thermotolerance of broiler under thermal stress.…”
Section: Strategies To Ameliorate Heat Stressmentioning
confidence: 91%
“…Increasing incubation temperature at 39.5°C during 12 h/day from E7 to E16 improved the feed conversion ratio of broilers compared to the control ( Piestun et al, 2013 ; Meteyake et al, 2020 ) without affecting broilers' growth compared to 24 h/day group which had lower body weights ( Piestun et al, 2008b ). According to Tzschentke and Hall (2009) , the FCR of short-term warm stimulated broilers (38.2–38.4°C, 2 h per day, from d17 onward) was significantly lower than in broilers of the control (37.2–37.4°C) and chronic warm (38.2–38.4°C, 24 h per day, from d17 onward) incubated groups.…”
Section: Incubation Temperature and Relative Humiditymentioning
confidence: 98%
“…The adverse effect of thermal stress on livestock has been a growing global concern [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] ]. Thermal stress occurs when the net quantity of energy moving from the animal's body to its surroundings and the amount of heat energy generated by the animal are out of balance [ 9 ] due to fluctuations in the weather elements.…”
Section: Introductionmentioning
confidence: 99%